The effect of Chitosan IFNα-pDNA Nanoparticle on the Pain induced by Varicella-zoster Virus in a Rat Model of Post-Herpetic Neuralgia - Jon, Hyok Ho; Han, Song Chan; Paek, Sinhyok; Paek, Sungil; Mun, Songchol (Medical Science Journal for Advance Research, 2026)
Background and Aim: Acute and chronic pain (post-herpetic neuralgia or PHN) are encountered in patients with herpes zoster that is caused by reactivation of varicella-zoster virus (VZV) from a state of neuronal latency. PHN is often refractory to current treatments, and additional strategies for pain relief are needed. The present study aims to assess the effects of Chitosan IFNα-pDNA Nanoparticle(CIN) on the pain induced by varicella-zoster virus in Sprague–Dawley rat model of post-herpetic neuralgia. Methods: : Rats were injected with 0.2mL of PBS, Chitosan IFNα-pDNA Nanoparticle( dose corresponding to 50μg pDNA in 1mL) and IFNα-pDNA(50μg/mL) 3 days before VZV infection. MA and TH ipsilateral/contralateral responses were measured according to days after VZV infection. And also rats inoculated with VZV and showing significant mechanical and thermal hypersensitivity by 19 days post infection were then inoculated at the same footpad with 0.2mL of PBS, Chitosan IFNα-pDNA Nanoparticle( dose corresponding to 50μg pDNA in 1mL) and IFNα-pDNA(50μg/mL). Animals receiving PBS, Chitosan IFNα-pDNA Nanoparticle(CIN) and IFNα-pDNA continued to measure MA and TH ipsilateral/contralateral responses according to days after vector administration. Results: Chitosan IFNα-pDNA Nanoparticle(CIN) effectively reduced chronic VZV-induced nocifensive indicators of pain such as mechanical allodynia(MA), thermal hyperalgesia (TH). Conclusion: These results indicate that administration of Chitosan IFNα-pDNA Nanoparticle(CIN) relieved VZV-induced pain and prophylactic CIN administration prevented VZV-induced pain from developing.